2022
DOI: 10.1093/neuonc/noac079.231
|View full text |Cite
|
Sign up to set email alerts
|

HGG-16. Final analysis of the HIT-HGG-2007 trial (ISRCTN19852453): Significant survival benefit for pontine and non-pontine pediatric high-grade gliomas in comparison to previous HIT-GBM-C/-D trials.

Abstract: The aim of the HIT-HGG-2007 trial (ISRCTN19852453) was to demonstrate therapeutic non-inferiority of temozolomide radiochemotherapy for pediatric patients (3-18 years) with high-grade gliomas (pedHGG) in comparison to the cisplatinum-based radiochemotherapy of the two previous clinical trials HIT-GBM-C/-D. Between 06/2009 and 12/2016, 456 patients were enrolled at 79 centers in Germany, Austria, and Switzerland (n=18 dropouts, remaining patients for confirmatory analysis: n=438). 438 patients from HIT-GBM-C/-D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…12 While the HIT-HGG-2007 study (ISRCTN registry identifier: ISRCTN19852453) showed non-inferiority of TMZ treatment compared with historical controls, final results have not yet been published. 13 Multiple attempts have also been made to combine TMZ with other chemotherapy agents to try to improve survival in patients with pHGG.…”
mentioning
confidence: 99%
“…12 While the HIT-HGG-2007 study (ISRCTN registry identifier: ISRCTN19852453) showed non-inferiority of TMZ treatment compared with historical controls, final results have not yet been published. 13 Multiple attempts have also been made to combine TMZ with other chemotherapy agents to try to improve survival in patients with pHGG.…”
mentioning
confidence: 99%